Prospects for the use of chitosan bioactive coatings for the prevention of infectious complications in dental implantation - Kirichek, O.; Albakr, Ahmed; Maksymenko, P.; Maksymenko, V. (Journal of Education, Health and Sport, 2025)
Background. The study is that for the first time the antibacterial and fungicidal properties of the chitosan-based bioactive coating FAR-5X were evaluated in comparison with traditional titanium materials for dental implantation. It was found that the chitosan coating is able to significantly inhibit the growth of Escherichia coli and Candida albicans due to the mechanism of agglutination of microbial cells, which provides a long-term bacteriostatic and fungicidal effect. The results showed that FAR-5X reduces the level of colonization of titanium surfaces tenfold compared to both pure titanium and control cultures, which confirms its high efficiency as an antimicrobial barrier. For the first time, it has been shown that the use of such a coating allows combining the osseointegration potential of titanium with the pronounced antimicrobial properties of chitosan, opening up new prospects for the creation of biocompatible implants with an increased level of protection against infectious complications. Aim. To evaluate the antibacterial and fungicidal properties of the chitosan-based FAR-5X coating in comparison with traditional materials for dental implantation. Materials and methods. The study was performed on VT-1 titanium disks divided into a control group and a group coated with FAR-5X. The disks were kept in a 50% aqueous solution of chitosan for 24 hours and dried. The antibacterial activity was evaluated against Escherichia coli and the fungicidal activity against Candida albicans according to ISO 27447:2009 by measuring optical density and cell counting. Cultures without contact with materials served as controls. Statistical processing was performed by methods of variation statistics with the assessment of probability by Student's test (p<0.05; p<0.01). Results. To reduce the growth of pathogenic microflora and improve osseointegration, VT-1 titanium disks were modified with FAR-5X coating based on a 50% aqueous chitosan solution. The antibacterial activity was evaluated against Escherichia coli and the fungicidal activity against Candida albicans according to ISO 27447:2009 by the method of optical density and cell counting. After 24 hours, the growth of E. coli on FAR-5X was 6 times lower than that of titanium and 12 times lower than that of the control (0.35±0.03; p<0.01), and after 96 hours - 28 times lower than that of titanium (0.20±0.02; p<0.001). Similarly, the growth of C. albicans on FAR-5X after 14 days was 10 times lower than that on titanium and more than 100 times lower than that on control (0.50±0.04; p<0.001). The data obtained confirm the high efficiency of FAR-5X in inhibiting the growth of bacteria and fungi compared to the standard titanium alloy. Conclusions. The FAR-5X coating significantly inhibits the growth of E. coli and C. albicans compared to the titanium alloy VT-1 and the control (p<0.001), demonstrating high antibacterial and fungicidal activity. ANOVA confirmed statistically significant differences, which makes FAR-5X a promising material for improving implant biocompatibility.